Design of kinetic well-matched Mo2C nanoparticles anchored into 3D hierarchical porous carbon towards high-rate sodium ion storage. (10th March 2021) - zhang, Dong-Ting; Liu, Mao-Cheng; Li, Jun; Zhang, Yu-Shan; Zhang, Bing-Mei; Lu, Chun; Hu, Yu-Xia; Wu, Kai-Peng; Kong, Ling-Bin
Highlights: A novel Mo2 C nanoparticles uniformly anchored into hierarchical porous carbon structure was achieved via a water-soluble NaCl template strategy. The interconnected heterogeneous porous framework promotes the fast Na + diffusion kinetics and provides a continuous ion transport path. HPC-Mo2 C architecture overcomes the intrinsic kinetics and capacity mismatch for high-rate sodium ion capacitor. The Na + storage kinetics performance of HPC-Mo2 C and pure Mo2 C were investigated by GITT. Abstract: Sodium ion capacitors (SICs) have attracted considerable attentions since it is integrating the complementary features of both high energy and power densities. One of the most crucial tasks for develop highly efficient SICs is to increase the faradaic Na + redox kinetics from the battery-type anode to match the electrical double-layer capacitance-type cathode. In this work, Mo2 C nanoparticles uniformly anchored into cross-linked hierarchical porous carbon (HPC-Mo2 C) have been produced by a water-soluble NaCl template strategy. The as-obtained HPC-Mo2 C composite shows a large specific surface area of 385.6 m 2 g −1 with well distributed micro– meso –macropores structure, delivering a superior rate capability (108.2 mAh g −1 at 5 A g −1 ) and robust long-term cycling of 190.6 mAh g −1 at 1 A g −1 after 2500 cycles. Electrochemical measurements illustrate that the Mo2 C nanoparticles uniformly anchored into cross-linked hierarchical porous structure can accelerate fast Na + diffusion kinetics toward excellent rate capacity and increase the pseudocapacitive behavior for the redox reaction. The SIC composed of HPC-Mo2 C as anode and activated carbon (AC) as cathode delivers an impressive energy density of 130.2 Wh kg −1 and ultra-high power density of 30, 000.0 W kg −1, as well as an unprecedented cycling stability of 88.9% retention after 10, 000 cycles with a potential range of 0–4.0 V. This work may cater to the requirements for rationale kinetic matching electrode for the advanced SICs.